Comparative study of insecticide resistance management strategies against brinjal shoot and fruit borer (Leucinodes orbonalis) (Lepidoptera: Crambidae) - SAHA, TAMOGHNA; CHANDRAN, NITHYA (The Indian Journal of Agricultural Sciences, 2021)
An experiment was conducted for kharif (2015-16 to 2017-18) in the field conditions to evaluate different insecticide usage tactics as resistance management strategies against Leucinodes orbonalis Guenee a serious shoot and fruit borer pest of brinjal (Solanu melongena L.). The results on bio-efficacy of insecticides revealed that in terms of shoot infestation, rotational strategy (chlorantraniliprole 18.5 SC @ 150 ml/ha followed by emmamectin benzoate 5 SG @ 200 ml/ha, spinosad45 SC @ 125 ml/ha, chorpyrifos20EC @ 1000 ml/ha, cypermethrin 25 EC @ 250 ml/ha) was significantly effective and recorded least per cent shoot infestation as compared to other resistance management strategies. Rotational strategy was highly effective in reducing fruit infestation and it was followed by chlorantraniliprole 18.5 SC, emmamectin benzoate 5SG and Spinosad 45 SC which comes under sequential strategy. Fruit yield obtained highest i.e. 360 q/ha with rotational strategy, however due to higher cost of chemicals, benefit cost ratio was found to be low but net profit was highest and it was followed by sequential strategy and mixture strategy. Based on the overall mean population of natural enemy, i.e. coccinellids (Cheilomenes sexmaculata and Coccinella septempunctata) it was apparent that the majority of the newer molecules were safer to the predator. Hence, rotational strategy, i.e. spraying of chlorantraniliprole 18.5 SC, emmamectin benzoate 5 SG, spinosad45 SC, chorpyrifos 20 EC and cypermethrin25 EC at 15 days interval can be used as a new tool by farmers for effective management against L. orbonalis.